The Impact of Corporate Social Responsibility on Accrual Earnings Management and Real Earnings Management - Soliyah Wulandari (ETIKONOMI, 2016)
This study examines the influence of Corporate Social Responsibility on accrual earnings management and real earnings management. This study using control variables company size, KAP quality, and leverage. Sample of this study Obtained with purposive sampling for all non-financial company listed in the Indonesia Stock Exchange from 2001 to 2012. This study will use the data secondary, such as annual report. Data analysis will perform using multiple regressions. Result show that Corporate Social Responsibility is influence to accrual earnings management. Corporate Social Responsibility is a real influence to both abnormal earnings management of cash flow from operations and abnormal of production costsDOI: 10.15408/etk.v15i1.3116